Perceptions of the impact of accountability on the role of principals. - James E. Lyons; Bob Algozzine (Arizona State University, 2006)
Calls for accountability in America's schools have created increased responsibilities for educational leaders. In this article, we describe and discuss a study of elementary, middle, and high school principals' perceptions of the state-wide educational accountability program in North Carolina. The respondents indicated that the state's accountability program has had its greatest impact on how they monitored student achievement, aligned the curriculum to the testing program, provided student remedial or tutorial opportunities, assigned teachers to grades levels or subjects, and protected instructional time. Views of some components, such as measures of school effectiveness, school safety standards, expectations and promotion standards for students, and financial bonuses received by staff members in schools that meet expected achievement standards, were viewed favorably. In contrast, the No Child Left Behind Adequate Yearly Progress (AYP) requirement (incorporated into the state's accountability program), testing requirements for Limited English Proficiency students and special education students, the sanctions applied to schools that do not meet expected growth, and the school status designation labels that are applied to schools based upon student achievement were perceived more negatively. The predictable and unpredictable outcomes of a mandated accountability program on the perceptions (and behavior) of school principals create important considerations which are discussed for policy-makers and other professionals dealing with standards-based reform.